A generic formal model for the comparison and analysis of distributed job-scheduling algorithms in grid environment - Hafaiedh, Imene Ben (Journal of parallel and distributed computing, 2019)
Nowadays, high-end Systems consist of thousands of individual devices which are in general heterogeneous. Grid computing environments are an example of high-end systems which are composed of many diverse and heterogeneous resources distributed within multiple geographical areas. The performance of such systems depends considerably on job scheduling and resource allocation algorithms. Indeed, to improve the global throughput of these environments, effective and efficient load balancing algorithms are fundamentally important. In this paper, we propose a completely distributed formal model for the description of grid architecture. Our model, is then parameterized to describe different job-scheduling algorithms in a completely parallel architecture. In particular, we focus on the modeling and description of distributed load-balancing algorithms. To reach this purpose, we define a set of parallel schedulers communicating together to achieve a given load-balancing policy. To show the applicability of our approach, we propose to specify and compare different well-known job-scheduling policies in grid environments. The formal verification of different properties of the studied protocols has been performed automatically using Model-checking and a set of performance analysis results are also provided. •A generic formal model for the description of a Grid architecture as a component-based system. A completely parallel model built as a set of communicating local-schedulers.•A completely distributed model built as a composition of a set of local schedulers communicating via a set of connectors (interactions). We believe that any distributed job-scheduling strategy could be easily implemented using interactions and priorities between these interactions.•The model is adapted to describe a set of well-known load-balancing protocols•We have conducted several formal verification experiments to prove a set of properties over the modeled protocols•We have performed a series of experiments to evaluate, analyze and compare the performance of the modeled protocols under a set of real-time executions for different configurations and metrics.